George Lukács dan Teori Kritis dalam Perkembangan Ilmu Komunikasi (1885 – 1971) - Mulyanti Syas (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2014)
One of social sciences  approach is a Critical Theory, which emerged as the release of economic determinism of orthodox Marxism. This approach seeks to reinvigorate philosophical thought of Karl Marx as the true revolutionary thinking. Georg Lukács was the first person who bring back the insights Hegelian dialectics in Marxism. Lukács rejected the economic determinism ('Marxisme Vulger') and more concerned with the processes of human consciousness in the life. The famous  thoughts from Lukács are ; reification, insight 'totality', the disclosure of 'positivism' and 'sociology contemplative' as an ideology that affirm the 'false' reality of bourgeois society, 'the unity of theory and praxis', the theory of 'revolutionary' and the task of 'objective' history.  Those thought  became the foundation of critical thinking in Communication Studies.